Good practices in the selfevaluation of graduate distance learning programs - Michel Jean Pierre Valdés-Montecinos; Susana Andrea Correa-Castillo; Margarita América Briceño-Toledo; Wendolin Margarita Suárez-Amaya (Universidad de Guadalajara, 2021)
The purpose of this essay is to share the good practices installed in the virtual postgraduate programs of the Universidad Arturo Prat (UNAP), Chile associated with the continuous evaluation of quality processes. Our focus is on the continuous improvement of good practices through the accreditation process with the Latin American and Caribbean Institute for Quality in Distance Education (CALED) and the self-evaluation that the institution carries out to deliver quality service. The methodology used in this work is the documentary review and description of experiences under a qualitative approach. The results reveal that the UNAP has promoted the self-evaluation and international certification of its programs, in a context of normative change in Chile, which establishes new criteria and standards under the new Law of Higher Education Nº v 21.091, in wich are recognized as good practices: the institutional policies, the planning of the selfevaluation process, the updates of the technological platform, the virtual education enviroment, the virtualization adequate to the context, the active-participative academic actions, the rol of the teacher and the student, the academic training, as well as the components of the self-evaluation process, that must be constantly monitored and evaluated, in order to deliver quality services in the training of people participating in graduate programs under the virtual learning modality.